2012
DOI: 10.1093/alcalc/ags120
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Thiamine is Still Important in Alcohol Dependence

Abstract: Reduced blood levels of thiamine in people who are alcohol dependent, compared with those with no history of alcohol abuse, are likely to be because of the poor diet. Consumption of vitamin supplements appears to bring thiamine levels closer to those seen in control participants. Supplementation of dietary intake of thiamine in people who are alcohol dependent remains an important measure for the prevention of Wernicke-Korsakoff's syndrome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Despite the introduction of mandatory and voluntary fortification with thiamine in staple grain foods such as bread in both developing and developed countries, the studies reported on in this review did not review participant dietary patterns to identify food based thiamine intake prior to supplementation. Oral thiamine supplementation may still remain important for those with alcohol dependence following inpatient alcohol withdrawal, from a nutrient adequacy and utilisation perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of mandatory and voluntary fortification with thiamine in staple grain foods such as bread in both developing and developed countries, the studies reported on in this review did not review participant dietary patterns to identify food based thiamine intake prior to supplementation. Oral thiamine supplementation may still remain important for those with alcohol dependence following inpatient alcohol withdrawal, from a nutrient adequacy and utilisation perspective.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some other protective factor might have mediated the effects of alcohol on cognitive functioning. For example, Australia has a program of mandatory thiamine fortification of bread and wheat flour which is thought to protect against thiamine deficiency, a known problem in alcohol dependence and risk factor for Wernicke-Korsakoff syndrome [60,61]. This may be an important protective factor that should be considered in future research in this area, along with assessment of other elements of nutritional intake.…”
Section: Discussionmentioning
confidence: 99%
“…103,104 In addition, during alcohol withdrawal, it is recommended that thiamin be administered either orally or parenterally to offset the greater thiamin requirement. 104…”
Section: Alcoholismmentioning
confidence: 99%